Rhenium‐Catalyzed Arylation–Acyl Cyclization between Enol Lactones and Organomagnesium Halides: Facile Synthesis of Indenones. (1st June 2021) - Hu, Binjing; Cheng, Xinyi; Hu, Ying; Liu, Xingchen; Karaghiosoff, Konstantin; Li, Jie
Abstract: A set of rhenium‐catalyzed arylation–acyl cyclizations between (hetero)arylmagnesium halides and enol lactones through a cascade C(sp 2 )−C(sp 2 )/C(sp 2 )−C(sp 2 ) bond formation under mild reaction conditions has been developed. Indeed, a wide range of functional groups on both organomagnesium halides and enol lactones is well tolerated by the simple rhenium catalysis, thus furnishing polyfunctionalized indenones in one‐pot fashion and with complete control of the regioselectivity. Moreover, this approach also provides a straightforward synthetic route to neolignan and (iso)pauciflorol F. Mechanistic studies demonstrated that the reaction involves a sequence of syn‐carborhenation and intramolecular nucleophilic addition. Abstract : A range of functionalized organomagnesium halides and enol lactones underwent rhenium‐catalyzed sequential arylation–acyl cyclization under mild reaction conditions, thus providing an expedient route to polyfunctionalized indenones with complete control of regioselectivity. This approach features a broad substrate scope, excellent functional group tolerance, and synthetic utility in the straightforward synthesis of biologically relevant molecules.